Giant dielectric BaTiO3 ceramic material and preparation method and application thereof
By doping trace amounts of rare earth element oxides into barium titanate ceramic materials and adopting a specific preparation process, the problem of strong temperature and frequency dependence of the dielectric properties of barium titanate ceramic materials has been solved, and huge temperature and frequency ranges have been achieved. Improved dielectric properties.
Patent Information
- Application Number
- CN202310885631.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The existing barium titanate (BaTiO3) ceramic materials have insufficient research in the field of megadielectrics, and the dielectric properties are highly dependent on temperature and frequency, and the multiphase doping method has only improved stability but has not greatly improved dielectric properties.
Trace amounts of amphoteric rare earth element oxides are individually doped into BaTiO3 powder through solid-phase doping, and combined with specific preparation process technology, the giant dielectric properties of BaTiO3 ceramic materials can be achieved. Specific steps include wet ball milling mixing, drying, binder grinding, dry pressing and sintering.
The dielectric properties of BaTiO3 ceramic materials have been significantly improved within a wide temperature and wide frequency range. The dielectric constant is greater than or close to 104. The material is dense and has fine grains, making it suitable for applications such as electronic packaging.
Smart Images

Figure CN119330701A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of barium titanate ceramic dielectric materials, and in particular to a giant dielectric BaTiO3 ceramic material and a preparation method and application thereof. Background Art
[0002] In recent years, the miniaturization of electronic components and the development of high energy storage technology have put forward higher and higher requirements on the dielectric properties of energy storage materials. Giant dielectric materials usually refer to materials with a dielectric constant of 10 4 The above dielectric materials have broad application prospects in the field of microelectronic devices and play an important role in the miniaturization and high-speed development of devices. The most studied giant dielectric materials at present include doped calcium copper titanate (CCTO), doped nickel oxide (NiO), doped strontium titanate (SrTiO3) and doped titanium dioxide (TiO2). However, the most widely used barium titanate (BaTiO3) ceramic material has not been fully studied in the field of giant dielectrics. Therefore, in order to develop a wider range of applications of BaTiO3 ceramic materials in the field of high energy storage, it is imperative to study its giant dielectric properties. As we all know, pure BaTiO3 ceramics have phase change behavior at -55-150°C, which causes the dielectric properties to be temperature and frequency dependent, near the Curie temperature (~T c ) will have a maximum dielectric constant value (2000-5000). In order to improve the temperature dependence of BaTiO3, scientists have adopted multi-phase doping and achieved good results. However, previous studies on multi-phase doping only improved the temperature and frequency stability of dielectric properties, and did not significantly improve the dielectric properties of BaTiO3. Summary of the invention
[0003] In view of the above technical problems, the present invention provides a method for preparing giant dielectric BaTiO3 ceramic materials, which can achieve the giant dielectric properties of BaTiO3 ceramic materials in a wide temperature and frequency range by doping a trace amount of amphoteric rare earth element oxides into BaTiO3 powder by solid phase doping, and combining with a specific preparation process technology. The process of the present invention is simple and easy to implement, and can be easily mass-produced.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] In one aspect, the present invention provides a method for preparing a giant dielectric BaTiO3 ceramic material, comprising the following steps:
[0006] (1) mixing barium titanate powder and rare earth oxide powder by wet ball milling;
[0007] (2) drying the mixed slurry after ball milling to obtain a powder, then adding a binder to grind and granulate the powder, and dry-pressing the powder;
[0008] (3) sintering the sample obtained by dry pressing to obtain the giant dielectric BaTiO3 ceramic material;
[0009] Based on 100 mol of the barium titanate powder, the doping amount of the rare earth oxide powder is: 0<rare earth oxide powder<0.7 mol; the sintering temperature is 1250-1300°C.
[0010] In some specific embodiments, based on 100 mol of the barium titanate powder, the doping amount of the rare earth oxide powder is 0.05 mol, 0.1 mol, 0.15 mol, 0.2 mol, 0.25 mol, 0.3 mol, 0.35 mol, 0.4 mol, 0.45 mol, 0.5 mol, 0.55 mol, 0.6 mol, 0.65 mol or any doping amount therebetween.
[0011] As a preferred embodiment, the particle size of the barium titanate powder is 100nm to 500nm, for example, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm or any particle size therebetween.
[0012] As a preferred embodiment, the particle size of the rare earth oxide powder is 50nm to 100nm.
[0013] As a preferred embodiment, the rare earth oxide powder is Re2O3, wherein Re is selected from at least one of Y, Gd, Tb, Dy, Ho and Er.
[0014] As a preferred embodiment, in step (1), the particle size of the ball milling medium is 1 mm to 3 mm;
[0015] Preferably, the ball milling speed is 350 rpm to 480 rpm, and the time is 12 h to 24 h.
[0016] As a preferred embodiment, in step (2), the drying temperature is 60°C to 100°C, and the drying time is 8h to 10h;
[0017] Preferably, the binder is a PVA solution with a concentration of 7 to 10 wt%;
[0018] Preferably, the mass of the binder is 10wt% to 17wt% of the mass of the powder;
[0019] Preferably, the pressure in the dry pressing molding is 300Mpa to 380Mpa.
[0020] In certain specific embodiments, in step (2), the drying further comprises grinding and sieving; the sieving is sieving through a 60-100 mesh sieve.
[0021] In certain specific embodiments, in step (2), the adding of binder and grinding and granulation is grinding after adding binder, and then sieving and granulation; the sieving is sieving through a 60-100 mesh sieve.
[0022] As a preferred embodiment, in step (3), the sintering temperature rising process is a staged temperature rising process, including three stages of heat preservation processes; the three stages of heat preservation processes are respectively:
[0023] The first stage: heating from room temperature to T1 temperature, and then keeping warm;
[0024] The second stage: heating from temperature T1 to temperature T2, and then keeping warm;
[0025] The third stage: heating from T2 temperature to the highest sintering temperature, and then keeping warm;
[0026] Among them, the temperature of T1 is 200℃~300℃; the temperature of T2 is 500℃~700℃.
[0027] As a preferred implementation mode, in step (3), the heating rate of the first stage is 1°C to 3°C / min, and the insulation time is 30min to 60min; the heating rate of the second stage is 1°C to 3°C / min, and the insulation time is 30min to 60min; the heating rate of the third stage is 3°C to 5°C / min, and the insulation time is 90min to 150min.
[0028] In another aspect, the present invention provides a giant dielectric BaTiO3 ceramic material obtained by the above preparation method.
[0029] In another aspect, the present invention provides use of the giant dielectric BaTiO3 ceramic material in electronic packaging.
[0030] The above technical solution has the following advantages or beneficial effects:
[0031] In the giant dielectric BaTiO3 ceramic material provided by the present invention, doping with rare earth elements can not only promote sintering, but also effectively inhibit the grain growth of barium titanate; and after sintering at 1200-1300°C, the temperature of the ceramic material is 1Hz-10Hz. 4 In the Hz frequency range, at -60℃~200℃, the dielectric constant is greater than or close to 10 4 Therefore, the giant dielectric BaTiO3 ceramic material provided by the present invention is not only dense and fine-grained, but also has giant dielectric properties in a wide temperature and frequency range. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 3 is a graph showing the dielectric constants of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 1 of the present invention changing with temperature and frequency.
[0033] Figure 2 It is a microscopic morphology of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 1 of the present invention.
[0034] Figure 3 This is a graph showing the dielectric constants of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 2 of the present invention as a function of temperature and frequency.
[0035] Figure 4 It is a microscopic morphology of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 2 of the present invention.
[0036] Figure 5 This is a graph showing the dielectric constants of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 3 of the present invention changing with temperature and frequency.
[0037] Figure 6 It is a microscopic morphology of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 3 of the present invention.
[0038] Figure 7 This is a graph showing the dielectric constants of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 4 of the present invention changing with temperature and frequency.
[0039] Figure 8 It is a microscopic morphology of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 4 of the present invention.
[0040] Fig. 9 This is a graph showing the dielectric constants of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 5 of the present invention changing with temperature and frequency.
[0041] Fig.10 It is a microscopic morphology of the giant dielectric BaTiO3 ceramic material and pure BaTiO3 in Example 5 of the present invention.
[0042] Fig.11 This is a graph showing the dielectric constant of the 0.9 mol % Dy2O3-BaTiO3 ceramic material in Comparative Example 1 of the present invention changing with temperature and frequency.
[0043] Fig.12 It is a microscopic morphology of the 0.9 mol% Dy2O3-BaTiO3 ceramic material in Comparative Example 1 of the present invention.
[0044] Fig.13This is a graph showing the dielectric constant of the 0.10 mol % Dy2O3-BaTiO3 ceramic material in Comparative Example 2 of the present invention changing with temperature and frequency. DETAILED DESCRIPTION
[0045] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0046] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0047] Embodiment 1:
[0048] The giant dielectric BaTiO3 ceramic material in this embodiment is 0.05mol% Dy2O3-BaTiO3, and the preparation method is as follows:
[0049] 1) Pour industrial-grade BaTiO3 powder with a particle size of 250 nm into a 100 mL zirconia ball mill, add 0.05 mol of Dy2O3 with a purity of 99.9% and a particle size of 100 nm as a dopant, and stir manually with a glass rod for 1 to 3 minutes to mix the dry powder evenly;
[0050] 2) Add anhydrous ethanol in a mass ratio of 1:1 to BaTiO3 powder into the ball mill, add zirconia grinding balls with a diameter of 3 mm in a mass ratio of 1.5:1, and stir manually with a glass rod for 1 min to 3 min to mix evenly; then install the ball mill on a planetary ball mill for mechanical wet ball milling, set the speed to 480 rpm, and set the ball milling time to 24 h;
[0051] 3) The mixed slurry after ball milling is separated into balls, and then dried in an oven at 80° C. for 10 hours; during the drying process, the container containing the mixed slurry should be sealed with a breathable and high-temperature resistant material to prevent the drying debris from falling into it; the dried powder is ground in an agate mortar, and then sieved with a 60-mesh sieve to obtain 0.05 mol% Dy2O3-BaTiO3 powder;
[0052] 4) Grind 10 g of the sieved powder and 1.5 g of 8 wt% PVA binder solution in an agate mortar until the powder particles are distinct; sieve through a 60-mesh sieve for granulation;
[0053] 5) Pour 0.3 g of the granulated powder into a stainless steel mold with a diameter of 12 mm and press it using a dry press at a pressure of 375 MPa;
[0054] 6) sintering the sample obtained by dry pressing in a muffle furnace to obtain a giant dielectric BaTiO3 ceramic material; wherein the sintering atmosphere is air, the sintering temperature is set to 1300°C, and the sintering pressure is normal pressure;
[0055] The sintering temperature rise process is a three-stage process:
[0056] The first stage: heating from room temperature to 300°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0057] The second stage: heating from 300°C to 600°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0058] The third stage: heating from 600°C to 1300°C at a heating rate of 5°C / min, and then keeping warm for 120 minutes.
[0059] In this embodiment, the giant dielectric BaTiO3 ceramic material is polished with 1000-mesh sandpaper, ultrasonically cleaned in alcohol for 15 minutes, and then dried in an oven at 100°C for 8 hours; then, a silver electrode is plated on it, and then sintered in a muffle furnace at a sintering temperature of 750°C; after removing excess silver electrodes around the sintered silver-plated electrode sample, a dielectric property test is performed, and the test instrument is an Agilent high and low temperature dielectric thermometer, the test voltage is 1V, the test temperature is -60°C to 200°C; the test frequency is 1Hz to 10 5 Hz, test results see Figure 1 .
[0060] In this embodiment, the giant dielectric BaTiO3 ceramic material is subjected to grinding, polishing and thermal etching, and a field emission scanning electron microscope is used to perform microscopic morphology testing. The test results are shown in FIG. Figure 2 .
[0061] from Figure 1 It can be seen that the dielectric constant of the giant dielectric BaTiO3 ceramic material (0.05mol% Dy-BT-1300) in this embodiment is significantly higher than that of the pure BaTiO3 ceramic material (BT) with silver-plated electrodes under the same conditions. 3 Hz, when the temperature is -60℃~200℃, the dielectric constant is close to or greater than 10 4 While the dielectric constant of pure BT is within this range, it is only 700 to 3700. Therefore, the giant dielectric BaTiO3 ceramic material can be prepared in this embodiment.
[0062] from Figure 2 It can be clearly seen that the grain size (~0.82μm) of 0.05mol% Dy-BT ceramic material is significantly smaller than the grain size (~1.98μm) of pure BT ceramic material prepared under the same conditions, indicating that doping with 0.05mol% Dy2O3 can inhibit the growth of BaTiO3 ceramic grains.
[0063] Embodiment 2:
[0064] The giant dielectric BaTiO3 ceramic material in this embodiment is 0.10mol% Dy2O3-BaTiO3, and the preparation method is as follows:
[0065] 1) Pour industrial-grade BaTiO3 powder with a particle size of 250 nm into a 100 mL zirconia ball mill, add 0.10 mol of Dy2O3 with a purity of 99.9% and a particle size of 100 nm as a dopant, and stir manually with a glass rod for 1 min to 3 min to mix the dry powder evenly;
[0066] 2) Add anhydrous ethanol in a mass ratio of 1:1 to BaTiO3 powder into the ball mill, add zirconia grinding balls with a diameter of 3 mm in a mass ratio of 1.5:1, and stir manually with a glass rod for 1 min to 3 min to mix evenly; then install the ball mill on a planetary ball mill for mechanical wet ball milling, set the speed to 480 rpm, and set the ball milling time to 24 h;
[0067] 3) The mixed slurry after ball milling is separated into balls, and then dried in an oven at 80° C. for 10 h; during the drying process, the container containing the mixed slurry should be sealed with a breathable and high-temperature resistant material to prevent the drying debris from falling into it; the dried powder is ground in an agate mortar, and then sieved with a 60-mesh sieve to obtain 0.10 mol% Dy2O3-BaTiO3 powder;
[0068] 4) Grind 10 g of the sieved powder and 1.5 g of 8 wt% PVA binder solution in an agate mortar until the powder particles are distinct; sieve through a 60-mesh sieve for granulation;
[0069] 5) Pour 0.3 g of the granulated powder into a stainless steel mold with a diameter of 12 mm and press it using a dry press at a pressure of 375 MPa;
[0070] 6) sintering the sample obtained by dry pressing in a muffle furnace to obtain a giant dielectric BaTiO3 ceramic material; wherein the sintering atmosphere is air, the sintering temperature is set to 1300°C, and the sintering pressure is normal pressure;
[0071] The sintering temperature rise process is a three-stage process:
[0072] The first stage: heating from room temperature to 300°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0073] The second stage: heating from 300°C to 600°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0074] The third stage: heating from 600°C to 1300°C at a heating rate of 5°C / min, and then keeping warm for 120 minutes.
[0075] In this embodiment, the giant dielectric BaTiO3 ceramic material is polished with 1000-grit sandpaper, ultrasonically cleaned in alcohol for 15 minutes, and then dried in an oven at 100°C for 8 hours; then, the silver electrode is plated on it, and then sintered in a muffle furnace at a sintering temperature of 750°C; after removing the excess silver electrode around the silver-plated electrode sample, the dielectric property test is performed, and the test instrument is an Agilent high and low temperature dielectric thermometer, the test voltage is 1V, the test temperature is -60°C to 200°C; the test frequency is 1Hz to 10 5 Hz, test results see Figure 3 .
[0076] In this embodiment, the giant dielectric BaTiO3 ceramic material is subjected to grinding, polishing and thermal etching, and a field emission scanning electron microscope is used to perform microscopic morphology testing. The test results are shown in FIG. Figure 4 .
[0077] As can be seen from FIG. 3, the giant dielectric BaTiO3 ceramic material (0.10 mol% Dy-BT-1300) in this embodiment has a high dielectric constant at frequencies of 1 Hz to 10 5 Hz, when the temperature is -60℃~200℃, the dielectric constant is greater than 10 4 , which is significantly higher than that of pure BT ceramic materials.
[0078] from Figure 4 It can be clearly seen that the grain size (~0.74μm) of 0.10mol% Dy-BT ceramic material is significantly smaller than the grain size (~1.98μm) of pure BT ceramic material prepared under the same conditions, indicating that doping with 0.10mol% Dy2O3 can inhibit the growth of BaTiO3 grains.
[0079] Embodiment 3:
[0080] The giant dielectric BaTiO3 ceramic material in this embodiment is 0.15mol% Dy2O3-BaTiO3, and the preparation method is as follows:
[0081] 1) Pour industrial-grade BaTiO3 powder with a particle size of 250 nm into a 100 mL zirconia ball mill, add 0.15 mol of Dy2O3 with a purity of 99.9% and a particle size of 100 nm as a dopant based on 100 mol of BaTiO3 powder, and stir manually with a glass rod for 1 min to 3 min to mix the dry powder evenly;
[0082] 2) Add anhydrous ethanol in a mass ratio of 1:1 to BaTiO3 powder into the ball mill, add zirconia grinding balls with a diameter of 3 mm in a mass ratio of 1.5:1, and stir manually with a glass rod for 1 min to 3 min to mix evenly; then install the ball mill on a planetary ball mill for mechanical wet ball milling, set the speed to 480 rpm, and set the ball milling time to 24 h;
[0083] 3) The mixed slurry after ball milling is separated into balls, and then dried in an oven at 80° C. for 10 hours; during the drying process, the container containing the mixed slurry should be sealed with a breathable and high-temperature resistant material to prevent the drying debris from falling into it; the dried powder is ground in an agate mortar, and then sieved with a 60-mesh sieve to obtain 0.15 mol% Dy2O3-BaTiO3 powder;
[0084] 4) Grind 10 g of the sieved powder and 1.5 g of 8 wt% PVA binder solution in an agate mortar until the powder particles are distinct; sieve through a 60-mesh sieve for granulation;
[0085] 5) Pour 0.3 g of the granulated powder into a stainless steel mold with a diameter of 12 mm and press it using a dry press at a pressure of 375 MPa;
[0086] 6) sintering the sample obtained by dry pressing in a muffle furnace to obtain a giant dielectric BaTiO3 ceramic material; wherein the sintering atmosphere is air, the sintering temperature is set to 1300°C, and the sintering pressure is normal pressure;
[0087] The sintering temperature rise process is a three-stage process:
[0088] The first stage: heating from room temperature to 300°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0089] The second stage: heating from 300°C to 600°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0090] The third stage: heating from 600°C to 1300°C at a heating rate of 5°C / min, and then keeping warm for 120 minutes.
[0091] In this embodiment, the giant dielectric BaTiO3 ceramic material is polished with 1000-grit sandpaper, ultrasonically cleaned in alcohol for 15 minutes, and then dried in an oven at 100°C for 8 hours; then, the silver electrode is plated on it, and then sintered in a muffle furnace at a sintering temperature of 750°C; after removing the excess silver electrode around the silver-plated electrode sample, the dielectric property test is performed, and the test instrument is an Agilent high and low temperature dielectric thermometer, the test voltage is 1V, the test temperature is -60°C to 200°C; the test frequency is 1Hz to 10 5 Hz, test results see Figure 5 .
[0092] In this embodiment, the giant dielectric BaTiO3 ceramic material is subjected to grinding, polishing and thermal etching, and a field emission scanning electron microscope is used to perform microscopic morphology testing. The test results are shown in FIG. Figure 6 .
[0093] from Figure 5 It can be seen from the figure that the giant dielectric BaTiO3 ceramic material (0.15mol% Dy-BT-1300) in this embodiment has a high dielectric constant at frequencies of 1 Hz to 10 4 Hz, when the temperature is -60℃~200℃, the dielectric constant is greater than 10 4 , which is significantly higher than that of pure BT ceramic materials.
[0094] from Figure 6 It can be clearly seen that the grain size of 0.15mol% Dy-BT ceramics (~0.83μm) is significantly smaller than the grain size of pure BT ceramic materials prepared under the same conditions (~1.98μm), indicating that doping with 0.15mol% Dy2O3 can inhibit the growth of BaTiO3 grains.
[0095] Embodiment 4:
[0096] The giant dielectric BaTiO3 ceramic material in this embodiment is 0.50mol% Y2O3-BaTiO3, and the preparation method is as follows:
[0097] 1) Pour industrial-grade BaTiO3 powder with a particle size of 250nm into a 100mL zirconia ball mill, add 0.50 mo of Y2O3 with a purity of 99.9% and a particle size of 50nm as a dopant based on 100mol of BaTiO3 powder, and stir manually with a glass rod for 1min to 3min to mix the dry powder evenly;
[0098] 2) Add anhydrous ethanol in a mass ratio of 1:1 to BaTiO3 powder into the ball mill, add zirconia grinding balls with a diameter of 3 mm in a mass ratio of 1.5:1, and stir manually with a glass rod for 1 min to 3 min to mix evenly; then install the ball mill on a planetary ball mill for mechanical wet ball milling, set the speed to 480 rpm, and set the ball milling time to 24 h;
[0099] 3) The mixed slurry after ball milling is separated into balls, and then dried in an oven at 80° C. for 10 hours; during the drying process, the container containing the mixed slurry should be sealed with a breathable and high-temperature resistant material to prevent the drying debris from falling into it; the dried powder is ground in an agate mortar, and then sieved with a 60-mesh sieve to obtain 0.50 mol% Y2O3-BaTiO3 powder;
[0100] 4) Grind 10 g of the sieved powder and 1.5 g of 8 wt% PVA binder solution in an agate mortar until the powder particles are distinct; sieve through a 60-mesh sieve for granulation;
[0101] 5) Pour 0.3 g of the granulated powder into a stainless steel mold with a diameter of 12 mm and press it using a dry press at a pressure of 380 MPa;
[0102] 6) sintering the sample obtained by dry pressing in a muffle furnace to obtain a giant dielectric BaTiO3 ceramic material; wherein the sintering atmosphere is air, the sintering temperature is set to 1250°C, and the sintering pressure is normal pressure;
[0103] The sintering temperature rise process is a three-stage process:
[0104] The first stage: heating from room temperature to 300°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0105] The second stage: heating from 300°C to 600°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0106] The third stage: heating from 600°C to 1250°C at a heating rate of 5°C / min, and then keeping warm for 120 minutes.
[0107] In this embodiment, the giant dielectric BaTiO3 ceramic material is polished with 1000-mesh sandpaper, ultrasonically cleaned in alcohol for 15 minutes, and then dried in an oven at 100°C for 8 hours; then, a silver electrode is plated on it, and then sintered in a muffle furnace at a sintering temperature of 750°C; after removing excess silver electrodes around the sintered silver-plated electrode sample, a dielectric property test is performed, and the test instrument is an Agilent high and low temperature dielectric thermometer, the test voltage is 1V, the test temperature is -60°C to 200°C; the test frequency is 1Hz to 10 5 Hz, test results see Figure 7 .
[0108] In this embodiment, the giant dielectric BaTiO3 ceramic material is subjected to grinding, polishing and thermal etching, and a field emission scanning electron microscope is used to perform microscopic morphology testing. The test results are shown in FIG. Figure 8 .
[0109] This embodiment also tests the volume density and relative density of the giant dielectric BaTiO3 ceramic material. The test method is the Archimedean drainage method, and the test solution is deionized water. The test results are shown in Table 1 below.
[0110] from Figure 7 It can be seen from the figure that the giant dielectric BaTiO3 ceramic material in this embodiment has a high dielectric constant at a frequency of 1 Hz to 10 3 Hz, when the temperature is -60℃~200℃, the dielectric constant is greater than 10 4 ; At a frequency of 10 4 When the temperature is 0~200℃, the dielectric constant is greater than 10 4 .
[0111] From Table 1 and Figure 8 It can be clearly seen that the volume density of 0.50mol% Y-BT ceramics is higher than that of pure BT ceramics, while the grain size (~1.07μm) is significantly smaller than the grain size (~1.78μm) of pure BT ceramic materials prepared under the same conditions, indicating that doping with 0.50mol% Y2O3 can promote the sintering of BT matrix and inhibit the growth of BaTiO3 grains.
[0112] This example also prepared and tested the volume density and relative density of pure BaTiO3, 0.1mol% Y2O3-BaTiO3, 0.3mol% Y2O3-BaTiO3 and 0.5mol% Y2O3-BaTiO3, as shown in Table 1 below. By comparison, it can be seen that doping with Y2O3 can promote the densification of BaTiO3, and as the doping amount increases, the sintering effect is stronger.
[0113] Table 1
[0114]
[0115] Embodiment 5:
[0116] The giant dielectric BaTiO3 ceramic material in this embodiment is 0.50mol% Ho2O3-BaTiO3, and the preparation method is as follows:
[0117] 1) Pour industrial-grade BaTiO3 powder with a particle size of 250 nm into a 100 mL zirconia ball mill, add 0.50 mol of Ho2O3 with a purity of 99.9% and a particle size of 100 nm as a dopant, and stir manually with a glass rod for 1 min to 3 min to mix the dry powder evenly;
[0118] 2) Add anhydrous ethanol in a mass ratio of 1:1 to BaTiO3 powder into the ball mill, add zirconia grinding balls with a diameter of 3 mm in a mass ratio of 1.5:1, and stir manually with a glass rod for 1 min to 3 min to mix evenly; then install the ball mill on a planetary ball mill for mechanical wet ball milling, set the speed to 480 rpm, and set the ball milling time to 24 h;
[0119] 3) The mixed slurry after ball milling is separated into balls, and then dried in an oven at 80° C. for 10 hours; during the drying process, the container containing the mixed slurry should be sealed with a breathable and high-temperature resistant material to prevent the drying debris from falling into it; the dried powder is ground in an agate mortar, and then sieved with a 60-mesh sieve to obtain 0.50 mol% Ho2O3-BaTiO3 powder;
[0120] 4) Grind 10 g of the sieved powder and 1.5 g of 8 wt% PVA binder solution in an agate mortar until the powder particles are distinct; sieve through a 60-mesh sieve for granulation;
[0121] 5) Pour 0.3 g of the granulated powder into a stainless steel mold with a diameter of 12 mm and press it using a dry press at a pressure of 380 MPa;
[0122] 6) sintering the sample obtained by dry pressing in a muffle furnace to obtain a giant dielectric BaTiO3 ceramic material; wherein the sintering atmosphere is air, the sintering temperature is set to 1250°C, and the sintering pressure is normal pressure;
[0123] The sintering temperature rise process is a three-stage process:
[0124] The first stage: heating from room temperature to 300°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0125] The second stage: heating from 300°C to 600°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0126] The third stage: heating from 600°C to 1250°C at a heating rate of 5°C / min, and then keeping warm for 120 minutes.
[0127] In this embodiment, the giant dielectric BaTiO3 ceramic material is polished with 1000-grit sandpaper, ultrasonically cleaned in alcohol for 15 minutes, and then dried in a 100°C oven for 8 hours; then, the silver electrode is plated on it, and then sintered in a muffle furnace at a sintering temperature of 750°C; after removing the excess silver electrode around the silver-plated electrode sample, the dielectric performance test is performed using an Agilent high and low temperature dielectric thermometer, the test voltage is 1V, the test temperature is -60°C to 200°C; the test frequency is 1Hz to 10 5 Hz, test results see Fig. 9 .
[0128] In this embodiment, the giant dielectric BaTiO3 ceramic material is subjected to grinding, polishing and thermal etching, and a field emission scanning electron microscope is used to perform microscopic morphology testing. The test results are shown in FIG. Fig.10 .
[0129] from Fig. 9 It can be seen from the figure that the giant dielectric BaTiO3 ceramic material in this embodiment has a high dielectric constant at a frequency of 1 Hz to 10 3 Hz, when the temperature is -60℃~200℃, the dielectric constant is greater than 10 4 , which is significantly higher than the dielectric constant of pure BT ceramics.
[0130] from Fig.10 It can be seen that the grain size of 0.50mol% Ho-BT ceramics (~0.83μm) is significantly smaller than the grain size of pure BT ceramic materials prepared under the same conditions (~1.78μm), indicating that doping with 0.50mol% Ho2O3 can inhibit the growth of BaTiO3 grains.
[0131] Comparative Example 1:
[0132] The BaTiO3 ceramic material in this comparative example is 0.90 mol% Dy2O3-BaTiO3, and the preparation method is the same as that in Example 1.
[0133] Fig.11 and Fig.12 The following are the curves of the dielectric constant of the 0.90 mol% Dy2O3-BaTiO3 ceramic material in this comparative example as a function of temperature and frequency and the microscopic morphology. Fig.11 and Fig.12 It can be seen that the grains of 0.90mol% Dy-BT ceramics are small, indicating that doping with 0.90mol% Dy2O3 can effectively inhibit the growth of BaTiO3 grains. In terms of dielectric constant, the ceramic material doped with 0.90mol% Dy2O3 has a good dielectric constant at a frequency of 1Hz~10 4 Hz, when the temperature is -60℃~200℃, the dielectric constant is 1000~8000, which is higher than that of pure BT ceramics, but does not meet the requirements of giant dielectric materials.
[0134] Comparative Example 2:
[0135] The BaTiO3 ceramic material in this comparative example is 0.10 mol% Dy2O3-BaTiO3, and the preparation method is the same as that in Example 2, except that the sintering temperature in step 6) is different. The details are as follows:
[0136] 6) sintering the sample obtained by dry pressing in a muffle furnace to obtain a giant dielectric BaTiO3 ceramic material; wherein the sintering atmosphere is air, the sintering temperature is set to 1150°C, and the sintering pressure is normal pressure;
[0137] The sintering temperature rise process is a three-stage process:
[0138] The first stage: heating from room temperature to 300°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0139] The second stage: heating from 300°C to 600°C at a heating rate of 1°C / min, and then keeping warm for 30 minutes;
[0140] 1) The third stage: heating from 600°C to 1150°C at a heating rate of 5°C / min, and then keeping warm for 120 min.
[0141] Fig.13 The figure shows the change curve of the dielectric constant of the 0.10mol% Dy2O3-BaTiO3 ceramic material in this comparative example with temperature and frequency. It can be seen from the figure that the ceramic material doped with 0.10mol% Dy2O3 has a dielectric constant of 1Hz~10Hz. 4 When the Hz temperature is -60℃~200℃, the dielectric constant is 3000~9600, which is higher than that of pure BT ceramics, but does not meet the requirements of giant dielectric materials.
[0142] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a giant dielectric BaTiO3 ceramic material, characterized in that: The following steps are involved: (1) mixing barium titanate powder and rare earth oxide powder by wet ball milling; (2) drying the mixed slurry after ball milling to obtain a powder, then adding a binder to grind and granulate the powder, and dry-pressing the powder; (3) sintering the sample obtained by dry pressing to obtain the giant dielectric BaTiO3 ceramic material; Based on 100 mol of the barium titanate powder, the doping amount of the rare earth oxide powder is: 0<rare earth oxide powder<0.7 mol; the sintering temperature is 1250-1300°C.
2. The preparation method according to claim 1, characterized in that: The particle size of the barium titanate powder is 100nm to 500nm.
3. The preparation method according to claim 1, characterized in that: The particle size of the rare earth oxide powder is 50nm to 100nm.
4. The preparation method according to claim 1, characterized in that: The rare earth oxide powder is Re2O3, wherein Re is selected from at least one of Y, Gd, Tb, Dy, Ho and Er.
5. The preparation method according to claim 1, characterized in that: In step (1), the particle size of the ball milling medium is 1 mm to 3 mm; Preferably, the ball mill has a rotation speed of 350 rpm to 480 rpm and a time of 12 h to 24 h.
6. The preparation method according to claim 1, characterized in that: In step (2), the drying temperature is 60°C to 100°C, and the drying time is 8h to 10h; Preferably, the binder is a PVA solution with a concentration of 7 to 10 wt%; Preferably, the mass of the binder is 10wt% to 17wt% of the mass of the powder; Preferably, the pressure in the dry pressing molding is 300Mpa to 380Mpa.
7. The preparation method according to claim 1, characterized in that: In step (3), the sintering temperature rising process is a staged temperature rising process, including three stages of heat preservation processes; the three stages of heat preservation processes are respectively: The first stage: heating from room temperature to T1 temperature, and then keeping warm; The second stage: heating from temperature T1 to temperature T2, and then keeping warm; The third stage: heating from T2 temperature to sintering temperature, and then keeping warm; Among them, the temperature of T1 is 200℃~300℃; the temperature of T2 is 500℃~700℃.
8. The preparation method according to claim 7, characterized in that: The heating rate of the first stage is 1°C to 3°C / min, and the insulation time is 30min to 60min; the heating rate of the second stage is 1°C to 3°C / min, and the insulation time is 30min to 60min; the heating rate of the third stage is 3°C to 5°C / min, and the insulation time is 90min to 150min.
9. The giant dielectric BaTiO3 ceramic material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the giant dielectric BaTiO3 ceramic material according to claim 9 in electronic packaging.
Citation Information
Patent Citations
Multi-layered ceramic capacitor dielectric material with giant dielectric constant and preparation method thereof
CN107686347A
BaTiO3-based fine-grain ceramic with giant dielectric constant, low loss and high resistivity and preparation method of BaTiO3-based fine-grain ceramic
CN114230335A
Rare earth element-doped barium titanate giant dielectric ceramic material and preparation method thereof
CN114436645A
Process for Preparing BaTiO3-based Dielectric Ceramicswith High Density and Ultra-Fine Grains
KR1020010068943A